Adsorption and Catalytic Properties of Co/ZSM-5 Zeolite Catalysts for CO Oxidation - Ludmila P. Oleksenko; Vitaly K. Yatsimirsky; German M. Telbiz; Larisa V. Lutsenko (Adsorption Science & Technology)
Studies were made of the adsorption and acidic properties, the coordination state of the Co ion in Co 2 +, Co 3 +-containing ZSM-5 zeolite systems and the catalytic activity of these zeolites in CO oxidation. A correlation was established between the catalytic activity of these Co-containing zeolites and the number of Brönsted acid sites on the surface and in the system bulk as obtained by different methods. The content of various forms of Co ion coordination states and the ratio of Brönsted to Lewis acidic sites at the surface of the Co-containing zeolites defined their activity in CO oxidation.